A GARANTIA DO MÍNIMO EXISTENCIAL FRENTE AO MERCADO DE TRABALHO INFORMAL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
In recent years, Brazil has faced the growth of the informal labor market, marked by increasing unemployment rates and phenomena such as uberization. This scenario has been intensified by the COVID-19 pandemic, bringing about devastating social and economic consequences. Therefore, this article aims to briefly discuss the issues surrounding informal work and the deterioration of quality of life in the country, considering the principles of the existential minimum and human dignity. It explores the enjoyment of basic rights and briefly touches upon the impact of informal labor on social security. The article employs an inductive and qualitative method, drawing insights from doctrinal research, scientific articles, and legislation to shed light on reflections on the subject. Key-words: Existential minimum. Human dignity. Informal labour. Uberization.